Potential Roles of Exercise-Induced Plasma Metabolites Linking Exercise to Health Benefits - Yang, Yong Ryoul; Kwon, Ki-Sun (Frontiers in Physiology, 2020)
Regular exercise has a myriad of health benefits. An increase in circulating exercise factors following exercise is a critical physiological response. Numerous studies have shown that exercise factors released from tissues during physical activity may contribute to health benefits via autocrine, paracrine, and endocrine mechanisms. Myokines, classified as proteins secreted from skeletal muscle, are representative exercise factors. The roles of myokines have been demonstrated in a variety of exercise-related functions linked to health benefits. In addition to myokines, metabolites are also exercise factors. Exercise changes the levels of various metabolites via metabolic reactions. Several studies have identified exercise-induced metabolites that positively influence organ functions. Here, we provide an overview of selected metabolites secreted into the circulation upon exercise.